Analysis of Financial Performance at PT Semen Indonesia (Persero), Tbk Listed on the Indonesia Stock Exchange - Junaedy, J.; Pattiasina, Victor (Manunggal Halim Jaya, 2023)
This study aims to determine the financial performance of PT Semen Indonesia (Persero), Tbk listed on the Indonesia Stock Exchange (IDX) based on profitability ratios during the 2020-2022 period. The type of data used in this study is quantitative data, namely data in the form of numbers or numbers. Quantitative data serves to determine the number or magnitude of an object to be studied. In this study, the quantitative data is the company's financial statements. The data source used in this research is secondary data, namely all data collected through library research and company data in the form of documents that can support writing. The analysis technique used to determine the company's financial performance in this study is the profitability ratio, namely Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Asset (ROA), and Return on Equity (ROE). The results of this study indicate that in general the company's financial performance based on profitability analysis is not efficient and not good. This is because the level of profitability is not stable so that it has decreased in three consecutive years and is still below the industry average. Thus, the company has not been able to manage its capital efficiently in generating profits.